2006
DOI: 10.1158/1541-7786.mcr-05-0157
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide Cooperates with NS398 to Inhibit Growth of Human Hepatocellular Carcinoma Cells through Effects on Apoptosis and G0-G1 Cell Cycle Arrest

Abstract: Chemotherapy to date has not been effective in the treatment of human hepatocellular carcinoma. More effective treatment strategies may involve combinations of agents with activity against hepatocellular carcinoma. Parthenolide, a nuclear factor-KB (NF-KB) inhibitor, and NS398, a cyclooxygenase (COX)-2 inhibitor, have been shown to individually suppress the growth of hepatocellular carcinoma cells in vitro. To investigate their effects in combination, three human hepatocellular carcinoma lines (Hep3B, HepG2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 67 publications
(67 reference statements)
2
16
0
2
Order By: Relevance
“…Previous studies have verified that parthenolide can inhibit activation of IKK in pancreatic and hepatocellular carcinoma cells lines (25,27). Here, we examined whether parthenolide has the same effect in human NSCLC lines.…”
Section: Ikk Kinase Complexmentioning
confidence: 90%
“…Previous studies have verified that parthenolide can inhibit activation of IKK in pancreatic and hepatocellular carcinoma cells lines (25,27). Here, we examined whether parthenolide has the same effect in human NSCLC lines.…”
Section: Ikk Kinase Complexmentioning
confidence: 90%
“…The anticancer potential of parthenolide has been described both in vitro (43,(46)(47)(48)(49) and on animal models (44,50). Moreover, it has been shown that parthenolide could reduce metastasis (50).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the cytostatic effects of low concentrations of PTL inhibit the growth of tumor lines by labeling the S-phase of BrdU cells, a mouse fibrosarcoma cell line, though the results were unclear (15). Ralstin et al found that PTL functions in cooperation with NS398 to inhibit the growth of human hepatocellular carcinoma cells by effects on apoptosis and G 0 /G 1 cell cycle arrest (16). In the present study, we investigated the kinetics of apoptosis induction and cell cycle distribution after 0, 6, 12, and 24 h of incubation with PTL, treatment with hyperthermia and combination treatment using flow cytometric analysis.…”
Section: Introductionmentioning
confidence: 89%
“…3). PTL may also be effective in combination with COX-2 inhibitors for the treatment of hepatocellular carcinoma, for example, combination treatment with PTL and NS398 altered the cell cycle distribution resulting in greater G 0 /G 1 accumulation, which increased apoptosis only in PLC cells, 1 of 3 human hepatocellular carcinoma lines, which may decrease the apoptotic threshold in cells (16). As for the cell cycle distribution of HL-60 and Jurkat cells with inactive NF-ÎșB, it was demonstrated that PTL induced transient cell arrest in the G 2 and M phases followed by apoptosis (46).…”
Section: Assessment Of Sub-g 1 Fraction With Flow Cytometric Distribumentioning
confidence: 99%